Carbon emissions and hospital pathology stewardship: a retrospective cohort analysis. Issue 4 (20th August 2022) - McAlister, Scott; Smyth, Brendan; Koprivic, Ivan; Luca Di Tanna, Gian; McGain, Forbes; Charlesworth, Kate; Brown, Mark A.; Konecny, Pam
Abstract: Background: As healthcare is responsible for 7% of Australia's carbon emissions, it was recognised that a policy implemented at St George Hospital, Sydney, to reduce non‐urgent pathology testing to 2 days per week and, on other days only if essential, would also result in a reduction in carbon emissions. The aim of the study was to measure the impact of this intervention on pathology collections and associated carbon emissions and pathology costs. Aims: To measure the impact of an intervention to reduce unnecessary testing on pathology collections and associated carbon emissions and pathology costs. Methods: The difference in the number of pathology collections, carbon dioxide equivalents (CO2 e) for five common blood tests and pathology cost per admission were compared between a 6‐month reference period and 6‐month intervention period. CO2 e were estimated from published pathology CO2 e impacts. Cost was derived from pathology billing records. Outcomes were modelled using multivariable negative binomial, generalised linear and logistic regression. Results: In total, 24 585 pathology collections in 5695 patients were identified. In adjusted analysis, the rate of collections was lower during the intervention period (rate ratio 0.90; 95% confidence interval (CI), 0.86–0.95; P < 0.001). This resulted in a reduction of 53 g CO2 e (95% CI, 24–83 g; P < 0.001) and $22 (95% CI, $9–$34; P = 0.001) in pathology fees per admission. The intervention was estimated to have saved 132 kg CO2 e (95% CI, 59–205 kg) and $53 573 (95% CI, 22 076–85 096). Conclusions: Reduction in unnecessary hospital pathology collections was associated with both carbon emission and cost savings. Pathology stewardship warrants further study as a potentially scalable, cost‐effective and incentivising pathway to lowering healthcare associated greenhouse gas emissions.